Encephalitozoon cuniculi infection in cats: European guidelines from the ABCD on prevention and management - Addie, Diane D.; Tasker, Séverine; Boucraut-Baralon, Corine; Belák, Sandor; Egberink, Herman; Frymus, Tadeusz; Hartmann, Katrin; Hofmann-Lehmann, Regina; Marsilio, Fulvio; Lloret, Albert; Pennisi, Maria Grazia; Thiry, Etienne; et al. (SAGE Publications Inc., 2020)
Overview: Encephalitozoon cuniculi is a common obligate intracellular microsporidian parasite of rabbits that is increasingly recognised as a pathogen of cats and other mammalian species. These guidelines aim to review the literature on feline E cuniculi infection and provide recommendations on prevention and management. Infection in cats: E cuniculi infection should be considered as a differential diagnosis in cases of feline uveitis and cataract formation. It is not significantly associated with either chronic kidney disease or meningoencephalitis. E cuniculi infection is more common in stray or feral cats than in pet cats. Diagnosis and treatment: Serological tests for antibody detection in the blood are easy to perform and can be useful for diagnosis, but their specificity is low as antibodies have been found in apparently healthy cats. PCR appears to be more sensitive than histopathology for diagnosis, and is more sensitive when performed on cataractous lenses compared with aqueous humour, although ease of sampling is an obvious limitation. Treatment is with fenbendazole for 3 weeks and phacoemulsification to remove microsporidia from cataractous lenses. Zoonotic risk: E cuniculi is a potential zoonotic agent, and there is a particular risk to immunocompromised humans posed by infected rabbits. Albeit infrequent, spore shedding has been identified in cats, so care should be taken around infected cats.
Keywords: Taverne